Vom "Projekt im Projekt" zur "Stadt in der Stadt"? Probleme der Governance und des Managements großer urbaner Entwicklungsvorhaben am Beispiel der Wissenschaftsstadt Belval, Luxemburg; From the "project within the project" to the "city within the city"? Governance and management problems in large urban development projects using the example of the science city Belval, Luxembourg - Annick Leick; Markus Hesse; Tom Becker (Raumforschung und Raumordnung / Spatial Research and Planning, 2020)
Dieser Beitrag behandelt das Thema der urbanen Neubaugebiete aus zwei spezifischen Perspektiven: Zum einen geht es nicht primär um das Wohnen, sondern um Wissenschaft und Forschung als Rahmenthema der Stadterweiterung, insbesondere Hochschulstandorte und Wissenschaftsparks. Zum anderen geht es um die Analyse städtischer Management- und Governance-Praktiken, vor allem die Herauslösung großer Vorhaben aus dem üblichen Kontext der Stadtplanung. Zentral ist hier die Definition dieser Vorhaben als "Projekt" und ihre Unterordnung unter einen spezifischen Steuerungsansatz. Im Kontext der Diskussion von Großprojekten und urbaner Governance ist die These dieses Beitrags, dass sich Projekte umso mehr als Fremdkörper in der Stadtplanung entfalten können (und damit das Ziel auf urbane Integration unterlaufen), umso weniger sie Gegenstand bewährter Planungsprozesse und regulatorischer Praktiken sind. Zur empirischen Illustration dieses Arguments dient die Wissenschaftsstadt Belval im Süden Luxemburgs, die seit 2003 realisiert wird und deren Entwicklung hier kritisch analysiert wird. Als generelle Schlussfolgerungen werden planerische Anforderungen an den Umgang mit großen Neubauvorhaben formuliert. – – The paper explores the issue of new urban development areas from two specific perspectives: on the one hand, rather than concentrating on housing, we address the question of science and research, in particular university locations and science parks, as a central guiding principle for urban expansion. On the other hand, the paper focuses on the analysis of urban management and governance practices and, more specifically, the disjoining of large projects from their common urban planning context. Emphasis is put on the fact that such undertakings are defined as 'projects' and that they are subordinated to a specific management approach. Amid debates concerning large-scale urban development projects and urban governance, we develop the thesis that the risk for projects to unfold as a sort of 'foreign matter' in the urban realm increases as the degree to which they are subject to proven planning processes and regulatory practices diminishes. This argument will be empirically illustrated with Belval, the science city in the south of Luxembourg, which is developed ever since 2003 and whose progress is critically assessed here. The general conclusions include planning requirements for dealing with new large-scale development projects.
Keywords: 710; Projektmanagement; Großprojekte; Wissenschaftsstandorte; urbane Governance; Luxemburg; Project management; Large-scale urban development projects; Science locations; Urban governance